Effect of dietary prebiotics and probiotics on snakehead (Channa striata) health : Haematology and disease resistance parameters against Aeromonas hydrophila - Mohammad Bodrul, Munir; Roshada, Hashim; Siti Azizah, Mohd Nor; Marsh, Terence, L (Universiti Malaysia Sarawak (UNIMAS), 2018)
This study examined the eﬀect of dietary prebiotics and probiotics after 16 weeks, followed by 8 weeks of post feeding trial with the control unsupplemented diet on haematological and immune response against Aeromonas hydrophila infection in Channa striata ﬁngerlings. Fish were raised on a 40% protein and 12% lipid feed containing three commercial prebiotics (β-glucan, GOS or galacto-oligosaccharide, MOS or mannan-oligosaccharide); and two probiotics- (Saccharomyces cerevisiae, Lactobacillus acidophilus), respectively and a control. Throughout the study, supplementation with dietary prebiotics and probiotics led to signiﬁcant (P < 0.05) improvement in the red blood cells, white blood cells, packed cell volume, haemoglobin concentration and serum protein level and lysozyme activities; and these improvements were eﬀective signiﬁcantly (P < 0.05) when the ﬁsh were challenged with Aeromonas hydrophila at the dose of 2×106. The disease resistance against A. hydrophila was higher signiﬁcantly (P < 0.05) in ﬁsh fed with probiotic feed supplements (L.acidophilus was highest) compared to prebiotics and control. The study is the ﬁrst to report the absence of diﬀerences in sustaining the eﬃcacies attained afterintakeofβ-glucan, GOSandMOSuponpost-feeding withanunsupplemented feed, over a prolonged period.